Modelling and simulation of supply chain resilience using complex system approaches - Tan, Wen Jun (Nanyang Technological University, 2020)
Due to the globalization and increased collaboration between firms, supply chains (SCs) are evolving into supply chain networks (SCNs). The dynamic business environment and growing complexity of global SCNs lead to increasing vulnerabilities in the SCNs to disruptions. Supply chain resilience (SCRES) offers an approach to build an SCN such that it can mitigate the impact of disruptions and provide effective response to recover from the disruptions in a timely manner. However, due to their complexities, it is a challenge to design resilient SCNs. An SCN can be generally characterized into microscopic behaviours and macroscopic properties. In this thesis, macroscopic properties of an SCN are modelled using graphs or system dynamics (SD) models; the microscopic behaviours of the SC operations are modelled using agent-based model (ABMs).